Monitoring blood biochemical indices during the lactogenesis and galactopoiesis stages in female dromedary camels (Camelus dromedarius) - CHIKHA, MARIA; KHENENOU, TAREK; GHERISSI, DJALEL EDDINE; NAIFAL-GABRI; RAMDANI, NACIRA; AKRICHE, SOUNDES; AICHA, MOUANE; EL-BAHR, SABRY MOHAMED (The Indian Journal of Animal Sciences, 2025)
This study aims to investigate the changes of biochemical blood parameters in female dromedary camels during lactogenesis and galactopoiesis in Algeria. Therefore, 56 serum samples were collected from females (monthly) for last four months antepartum (AP) and the first four months postpartum (PP) and biochemical profiles were investigated. The data were statistically analyzed using General Linear Model with repeated measures and Benferroni test as post-hoc test. Glucose increased significantly at the third month PP, with sudden decrease after that. Triglycerides peaked significantly in second month PP compared to fourth month PP and first month AP. Cholesterol elevated significantly at the third month PP comparatively to the first months AP and PP. Low-density lipoprotein increased significantly substantially from the second to the fourth month PP. High-density lipoprotein lowered significantly in the first month AP to rise substantially at third month PP. Calcium increased considerably from second to third months PP. A significant difference of iron was marked between the third month AP and the fourth month PP. Urea dropped abruptly at first month PP and elevated considerably in the second month PP. Creatinine marked a substantial rise from third to first month AP to decrease afterward. It increased significantly at third months PP compared to antepartum period. ALT indices of second month AP decreased notably in the second month PP. These findings indicate that lactogenesis and galactopoiesis period have substantial impacts on metabolites, proteins, hepatic enzymes, and minerals in the blood of female camels.